Prescription of statins at discharge and 1‐year risk of major clinical outcomes among acute coronary syndromes patients with extremely low LDL‐cholesterol in clinical pathways for acute coronary syndromes studies. Issue 9 (22nd September 2018) - Sun, Yihong; Xie, Gaoqiang; Patel, Anushka; Li, Shenshen; Zhao, Wei; Yang, Xingzi; Wu, Tao; Li, Min; Li, Xian; Du, Xin; Hu, Rong; Huo, Yong; et al.
Abstract: Objective: The aim of this study was to investigate statin description on discharge and the benefit on the long‐term outcomes in acute coronary syndromes (ACS) patients with very low baseline LDL‐cholesterol (LDL‐c). Methods: This is a post‐hoc analysis of 3374 ACS patients who were discharged alive and had baseline LDL‐c levels below 70 mg/dL (1.8 mmol/L). The propensity score of using statin was estimated with a multivariable Logistic model including patient's demography, social economic status, cardiovascular risk factors, subtype of the diagnosis, and treatments received during hospitalization and current LDL‐c level. The risk of major adverse cardiovascular events (MACEs) was compared between patients received and not‐received statin with Cox‐regression models adjusting for the propensity score plus other factors. A sensitivity analysis was done in propensity score matched patients. Results: Compared with nonstatin group, the incidence of MACE at 12 months after discharge was lower in the statin group (11.1% vs 5.8%; P < 0.001). The propensity score plus other factors‐adjusted hazard ratios for MACEs was significant (0.58; 95% CI: 0.39, 0.87). The effect showed a significant dose‐response relationship ( P for trend = 0.02). The results in analyses with propensity‐score matched participants were in consistent with above findings. Analyses on total mortality in 12 months showed similar results. Conclusions: Among ACS survivors with a very low baseline LDL‐c, low to moderate intensity statin therapy was associated significantly with lower risk of MACEs and total mortality at 12 months. The results suggested that ACS survivors should take statin regardless of the baseline of LDL‐c.